2009
DOI: 10.1038/sc.2009.134
|View full text |Cite
|
Sign up to set email alerts
|

Urethral versus suprapubic catheter: choosing the best bladder management for male spinal cord injury patients with indwelling catheters

Abstract: Objective: Bladder management for male patients with spinal cord injury (SCI) challenges the urologist to work around physical and social restrictions set forth by each patient. The objective of this study was to compare the complications associated with urethral catheter (UC) versus suprapubic tube (SPT) in patients with SCI. Methods: A retrospective review of records at Long Beach Veterans Hospital was carried out to identify SCI patients managed with SPT or UC. Chart review identified morbidities including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(57 citation statements)
references
References 15 publications
4
47
2
2
Order By: Relevance
“…A newer study 7 reported that almost every of the examined 45 SCI patients with SPC (mean SPC period 14.3 years) suffered at least one symptomatic UTI, but only 30% had more than one UTI per year, 15% had UTI accompanied by fever, 11% suffered catheter-associated septicaemia and 4% incurred pyelonephritis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…A newer study 7 reported that almost every of the examined 45 SCI patients with SPC (mean SPC period 14.3 years) suffered at least one symptomatic UTI, but only 30% had more than one UTI per year, 15% had UTI accompanied by fever, 11% suffered catheter-associated septicaemia and 4% incurred pyelonephritis.…”
Section: Discussionmentioning
confidence: 96%
“…Existing data are inconsistent, older trials reported high rates, whereas newer retrospective studies allocate constant kidney function even after decades of SPC usage. 3,6,7 A retrospective study concerning symptomatic UTI 3 compared 34 tetraplegic SPC patients (follow-up 8.6 years) with 27 SCI-IC patients (mainly paraplegics, follow-up 9.9 years). The incidence of symptomatic UTI was lower in the SPC group (12 vs 26%), but not significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 By comparing transurethral and suprapubic catheters, stating that the risks of the two are even, the authors create the impression that using any of these options may be a good choice for the long-term treatment of patients with spinal cord injury. In my view, this statement has to be put into perspective.…”
mentioning
confidence: 99%
“…Among the most common urinary catheter complications are: anaphylaxis (allergic reaction to latex), cytotoxicity and hypersensitivity [37 40], symptomatic bacterial infection [19,41 51], catheter blockage (due to calculi and encrustations) [52 60], catheter fracture and malignancy [61], hematuria (blood in urine) [ 52,59, 62 64], intravesical knotting [4, 65 67], inflammation (due to pyelonephritis and epididymitis) [44,56,[58][59]62,68], erosion and periurethral abscess [56,59,62], mechanical trauma (partial damage, perforation and urinary leakage) [11 12, 52, 55, 69 73], urethral fistulae [59,62], urethral stenosis and stricture [56,62,72], and urosepsis [62 63, 74 76]. While several studies have investigated the morbidity and mortality associated with urinary catheters [52,62], to date no comprehensive review has been performed which has focused specifically on identifying and analyzing important complications caused or exacerbated by the mechanical interaction (i.e., physical contact) between the catheter and urinary tract.…”
Section: Introductionmentioning
confidence: 99%